Higher Initial DNA Damage and Persistent Cell Cycle Arrest after Carbon Ion Irradiation Compared to X-irradiation in Prostate and Colon Cancer Cells - Suetens, Annelies; Konings, Katrien; Moreels, Marjan; Quintens, Roel; Verslegers, Mieke; Soors, Els; Tabury, Kevin; Grégoire, Vincent; Baatout, Sarah (Frontiers in Oncology, 2016)
The use of charged particle beams such as carbon ions is becoming a more and more attractive treatment option for cancer therapy. Given the precise absorbed dose-localization and an increased biological effectiveness, this form of therapy is much more advantageous compared to conventional radiotherapy, and is currently being used for treatment of specific cancer types. The high ballistic accuracy of particle beams deposits the maximal dose to the tumor, while damage to the surrounding healthy tissue is limited. In order to better understand the underlying mechanisms responsible for the increased biological effectiveness, we investigated the DNA damage and repair kinetics and cell cycle progression in two p53 mutant cell lines, more specifically a prostate (PC3) and colon (Caco-2) cancer cell line, after exposure to different radiation qualities. Cells were irradiated with various absorbed doses (0, 0.5, and 2 Gy) of accelerated 13C-ions at the GANIL facility (Caen, France) or with X-rays (0, 0.1, 0.5, 1, 2 and 5 Gy). Microscopic analysis of DNA double strand breaks showed dose-dependent increases in γ-H2AX foci numbers and foci occupancy after exposure to both types of irradiation, in both cell lines. However, 24h after exposure residual damage was more pronounced after lower doses of carbon ion irradiation compared to X-irradiation. Flow cytometric analysis showed carbon ion irradiation induced a permanent G2/M arrest in PC3 cells at lower doses (2 Gy) compared to X-rays (5 Gy), while in Caco-2 cells the G2/M arrest was transient after irradiation with X-rays (2 Gy and 5 Gy) but persistent after exposure to carbon ions (2 Gy).